Predictors of binge eating: relevance of BMI, emotional eating and sensivity to environmental food cues - Černelič-Bizjak, Maša (2022)
Purpose Understanding humans’ food intake practices is helpful in reducing health problems. The purpose of this study was to investigate the relationships between eating behaviours and binge eating and to examine the influence of sex and weight status on these relationships. Design/methodology/approach A total of seventy-eight participants (39 with overweight; mean age: 38.1 ± 6.3 years; body mass index [BMI]: 25 ± 5.7 kg/m2) underwent measurements of binge eating, eating styles and body compositions. A hierarchical multiple regression analysis was performed to predict binge eating as a function of eating styles and demographic variables. Findings Women presented higher levels of binge eating symptomatology and emotional eating than men. The analysis showed that age and gender did not emerge as important predictors of binge eating. In contrast, emotional and external eating and BMI were found to be important predictors of binge eating. The results indicate that higher emotional and external eating behaviour with higher BMI are important risk factors for binge eating in a non-clinical sample. Originality/value In this study, BMI was used as a causal factor rather than a consequence of deregulation of eating behaviour. An individual’s tendency to binge eat may be determined by BMI, emotional eating and sensitivity to environmental food stimuli. Understanding sex differences and causal relationships between eating behaviours is critical for the prevention and treatment of obesity and related health problems and for proper dietary management.